Expression of cytokeratin 19 in prostatic adenocarcinoma: a systematic review - Sina Shahshenas; Seyyed Mohammad Hosseini; Hossein Yarmohammadi; Masood Soltanipur; Mohammadreza Jalali Nadoushan (BMC Cancer)
Abstract Background Cytokeratins are intracellular proteins known as diagnostic biomarkers or prognostic factors for certain cancers. Cytokeratin 19 (CK-19) expression has been proven to have prognostic value for some cancers, but its relationship with others, such as prostate cancer (PCa), remains unclear. This systematic review article aimed to examine the relationship between CK-19 expression and prostate adenocarcinoma (PAC). Methods To include the eligible studies that detected CK-19 expression in PAC, published articles since June 2024 were found using PubMed, Scopus, and Web of Science databases. The “prostate cancer” and “cytokeratin 19” keywords and their Mesh term were used for search databases. Data from the included articles were extracted and tabulated. This study was performed using the PRISMA guidelines, and the JBI checklist was used for the quality assessment. The study protocol was registered in PROSPERO under the “CRD42023472637” code. Results Twenty-one studies were included. Eleven studies used reverse transcription polymerase chain reaction (RT-PCR) to investigate CK-19 expression, four used immunohistochemistry (IHC) staining, three used both one-step nucleic acid amplification (OSNA) and hematoxylin and eosin (H&E) methods, and three used the electrochemiluminescence (ECL) technique. CK-19 expression was detected in 301 patients among 619 patients. Additionally, only five out of 80 healthy donors were positive for CK-19 expression. Conclusion Available evidence indicates a correlation between CK-19 expression and PAC progression, with higher CK-19 levels associated with advanced stages and worse prognosis. The overall evidence suggests that CK-19 could serve as a diagnostic and prognostic marker in PAC.